2017
DOI: 10.1186/s12920-017-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale gene network analysis reveals the significance of extracellular matrix pathway and homeobox genes in acute myeloid leukemia: an introduction to the Pigengene package and its applications

Abstract: BackgroundThe distinct types of hematological malignancies have different biological mechanisms and prognoses. For instance, myelodysplastic syndrome (MDS) is generally indolent and low risk; however, it may transform into acute myeloid leukemia (AML), which is much more aggressive.MethodsWe develop a novel network analysis approach that uses expression of eigengenes to delineate the biological differences between these two diseases.ResultsWe find that specific genes in the extracellular matrix pathway are und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 87 publications
3
40
1
Order By: Relevance
“…They employed a sophisticated network analysis to identify the architecture of active gene regulatory networks in AML and found that the regulation of ECM modules is the most significant feature of AML transcriptional profile. 12 Of particular interest is the downregulation of matrix metalloproteinase 9 (MMP9) observed in both Foroushani et al's and our studies; a finding in contrast with the general idea that MMP9 is highly expressed in AML. 13 Yet, our systematic approach suggests a possible explanation to this.…”
Section: 3contrasting
confidence: 53%
“…They employed a sophisticated network analysis to identify the architecture of active gene regulatory networks in AML and found that the regulation of ECM modules is the most significant feature of AML transcriptional profile. 12 Of particular interest is the downregulation of matrix metalloproteinase 9 (MMP9) observed in both Foroushani et al's and our studies; a finding in contrast with the general idea that MMP9 is highly expressed in AML. 13 Yet, our systematic approach suggests a possible explanation to this.…”
Section: 3contrasting
confidence: 53%
“…Analysis of the gene set with HumanMine showed an unexpectedly high number of genes on chromosome 1 (Figure C). We identified the homologues of the genes of Module 5 in mouse and inferred the corresponding eigengene without changing the weights (Supplemental Note 2) . The inferred eigengene in the mouse data differentiated most mouse HCC and normal liver samples, but a few samples clustered with the wrong group (adjusted P ‐value = 0.001; Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…| 315 of Module 5 in mouse and inferred the corresponding eigengene without changing the weights (Supplemental Note 2). 23 The inferred eigengene in the mouse data differentiated most mouse HCC and normal liver samples, but a few samples clustered with the wrong group (adjusted P-value = 0.001; Figure 6D). Therefore, this gene module was not as accurate for distinguishing tumor versus normal liver in C3HeB/FeJ mice.…”
Section: Eigengene Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We have obtained several literature evidences [87,88] suggesting that there is association between PROS1 and the leukemia. In addition, we obtain several leukemia-related KEGG pathways (such as hsa04610: complement and coagulation cascades [89] having p- value = 5.68E-05) as well as Gene-Ontology-terms (viz., GO:BPs of negative regulation of wound healing (GO:0061045) [90,91] having p -value = 2.19E-09, regulation of response to wounding (GO:1903034) [90] having p -value = 2.78E-09, negative regulation of blood coagulation (GO:0030195) [92] ( p -value = 2.21E-08); GO:CCs of extracellular space (GO:0005615) [83] having p -value = 1.49E-33, extracellular region (GO:0005576) [93] having p -value = 3.91E-07, etc.) that are attached with PROS1.…”
Section: Applicationmentioning
confidence: 99%